Primary multiple malignant skin tumors: melanoma and basal cell carcinoma - Tatiana A. Gaydina; Anton S. Dvornikov; Olga I. Patsap; Raisa T. Tairova; Dmitriy A. Lange (State Scientific Center of Dermatovenereology and Cosmetology, 2023)
The incidence of skin melanoma in the world is growing every year. Despite advances in diagnostics, the identification of the primary focus of melanoma in some cases is still difficult. The natural course sometimes manifests only with the appearance of melanoma metastases, which can mimic other diseases. Patient S., 52 years old, was admitted to the FCBRN of FMBA of Russia with complaints on periodic systemic dizziness, headaches of a pressing nature, episodes of speech impairment over the past three months. According to the brain MRI-scan results, a volumetric formation of the left frontal lobe was revealed. Upon examination, two non-pigmented lesions were found on the skin of the scalp and forehead. Due to the presence of focal neurological symptoms, it was decided to remove the brain tumor using neurophysiological monitoring and the scalp skin lesion, with histological verification. Morphological diagnosis of the removed brain tumor was a metastasis of amelanotic epithelioid melanoma. The skin lesion was basal cell carcinoma. Thus, the patient had primarily multiple malignant tumors: metastatic melanoma and basal cell carcinoma. The primary focus of melanoma could not be identified by available noninvasive research methods. The patient was referred to an oncologist to decide on the tactics of further examination and treatment. To date, the patient has been treated according to the scheme sh0876 1 line 1 course of pembrolizumab 400 mg IV, cycle 42 days.